THE PLIGHT OF SOUTH AFRICAN WHISTLE-BLOWERS: SEARCHING FOR EFFECTIVE PROTECTION - Karin Calitz (Obiter, 2024)
Daily reports in the media about the extent of corruption in South Africa and the plight of whistle-blowers who dare to report it demonstrates the inadequacy of protective measures in South Africa. The murder of whistle-blower Babita Deokaran saw other whistle-blowers go into hiding, fearing for their own safety, and calls for urgent measures to be implemented to ensure the physical safety of whistle-blowers. The United Nations Convention Against Corruption (UNCAC) contains measures that could be implemented to protect the physical safety of whistle-blowers. Currently, the only legislation specifically protecting whistle-blowers in South Africa is the Protected Disclosures Act (PDA), which only protects against detriment in the workplace. A number of other statutes provide a measure of protection, but they are fragmented and by no means adequate. A legal comparison with the United Kingdom (UK), Ireland and the United States of America (US) may provide guidelines for reform in South Africa. The UK is currently debating the Protection for Whistleblowing Bill (Bill 27) in the House of Lords to improve protection for whistle-blowers. This Bill proposes to sever the required link to employment so that any person reporting wrongdoing will be protected if certain requirements are met. Bill 27 also establishes the Office of the Whistleblower, which has wide-ranging powers to protect whistle-blowers. The Irish Protected Disclosures (Amendment) Act 2022 was amended to broaden the definition of “worker” to include persons not previously protected and to establish an Office of the Commissioner similar to the Office of the Whistleblower in Bill 27, although with limited power. Neither the UK nor Ireland requires whistle-blowers to report in good faith; the focus is on the message instead of the messenger. Financial rewards for whistle-blowers in the US have proved to be highly successful and could be implemented in South Africa. It is recommended that physical protection of whistleblowers be prioritised, that a Whistle-Blowers’ Office with wide-ranging powers be established, that protection be extended to persons outside the employment relationship, that whistle-blowers be rewarded for reporting on wrongdoing in prescribed circumstances, that the burden of proof be reversed and that the good faith requirement for protection be dropped.